Stainless steel and titanium alloys coated with sulfated chitosan to improve hemocompatibility properties - Gomes, Sandy Danielle Lucindo; Arcanjo, Maria Rosiene Antunes; Silva, Francisca Raysse Mesquita; Leal, Luzia Kalyne Almeida Moreira; Claro, Ana Paula Rosifini Alves [UNESP]; Popat, Ketul; Vieira, Rodrigo Silveira (Springer, 2023)
The main drawbacks of blood-contacting metallic devices are corrosion and thrombus formation on the surface, so polymeric coatings have been proposed to improve its hemocompatibility. Sulfated chitosan (SC) was obtained from natural chitosan (NC) reaction with chlorosulfonic acid to be used as a coating for metallic surfaces. The sulfated chitosan showed no platelet aggregation, an extended clotting time, and non-toxicity to rat fibroblast L929 cells. In this study, stainless steel (SS) and titanium alloys modified with TiO2 nanotube (NTT) growth received a NC and SC coating. The titanium surface coated with sulfated chitosan presented the lowest percentage of platelet coverage area. Sulfated chitosan proved to be a promising material for use as a coating for metallic surfaces applied for cardiovascular devices.
Keywords: TiO2 nanotubes; Platelet adhesion; Surface functionalization; Platelet aggregation